Progenitor Cell Therapy for the Treatment of Central Nervous System Injury: A Review of the State of Current Clinical Trials - Peter A. Walker; Matthew T. Harting; Shinil K. Shah; Mary-Clare Day; Ramy El Khoury; Sean I. Savitz; James Baumgartner; Charles S. Cox (Stem Cells International)
Recent preclinical work investigating the role of progenitor cell therapies for central nervous system (CNS) injuries has shown potential neuroprotection in the setting of traumatic brain injury (TBI), spinal cord injury (SCI), and ischemic stroke. Mechanisms currently under investigation include engraftment and transdifferentiation, modulation of the locoregional inflammatory milieu, and modulation of the systemic immunologic/inflammatory response. While the exact mechanism of action remains controversial, the growing amount of preclinical data demonstrating the potential benefit associated with progenitor cell therapy for neurological injury warrants the development of well-controlled clinical trials to investigate therapeutic safety and efficacy. In this paper, we review the currently active or recently completed clinical trials investigating the safety and potential efficacy of bone marrow-derived progenitor cell therapies for the treatment of TBI, SCI, and ischemic stroke. Our review of the literature shows that while the preliminary clinical trials reviewed in this paper offer novel data supporting the potential efficacy of stem/progenitor cell therapies for CNS injury, a great deal of additional work is needed to ensure the safety, efficacy, and mechanisms of progenitor cell therapy prior to widespread clinical trials.